Relation between score for allergic rhinitis and immunoglobulin-E levels in the local population - Thejas, Saai Ram; Vijay Bharath Reddy, C. R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Allergic rhinitis (AR) is the most prevalent atopic disease in the world. It involves clinical hypersensitivity of the nasal mucosa to foreign substances mediated through immunoglobulin E antibodies. The quantitative Score for allergic rhinitis (SFAR) ranging between 0 and 16 has been in use from 2002. Methods: 240 patients diagnosed with Persistent allergic rhinitis (PAR) were taken to be part of the study after proper consent irrespective of the severity of symptoms. Each patient filled out the SFAR form before the treatment commenced. Serum IgE levels were noted and treatment was started which included oral and topical antihistamines, oral leukotriene receptor antagonists along with intranasal steroids. The IgE values were assessed along with the SFAR values side by side to look for any association. Results: It was noted that the individuals with identified triggers of allergy and those with a positive family history of allergy had a considerable higher IgE value as compared to those who did not. The ones with a trigger identified as a cause had a 54.88% higher IgE value. The ones with positive family history had 47.12% higher IgE than the ones without a history of allergy. Conclusions: Patients with well-defined trigger agents of allergy and positive family history of allergy are at a higher risk as they have a higher IgE value. They should be advised regular follow-ups and be monitored closely.